Loss of Ufsp1 does not cause major changes at the neuromuscular junction - Cristofer Calvo; Coalesco Smith; Taejeong Song; Fabian Montecino-Morales; Sakthivel Sadayappan; Douglas P. Millay; Minchul Kim (PLoS ONE, 2025)
UFMylation is a Ubiquitin-like post-translational modification involved in myriad of cellular processes. Enzymes involved in this pathway, including ligases and UFM1-specific proteases, are essential for development and homeostasis. Our previous transcriptomic analyses identified an enrichment of Ufsp1 at the neuromuscular junction of skeletal muscle cells. Ufsp1, one of the two UFM1 proteases, had been considered a pseudogene due to truncation of its catalytic domain in several species, including humans. However, recent findings revealed that Ufsp1 is translated from a non-canonical start codon in humans, yielding a catalytically active enzyme. This discovery has revived interest in studying Ufsp1’s role in vivo. We generated two mutant mouse models, one with a point mutation abolishing catalytic activity and another with complete knockout of the gene. Unlike other UFMylation pathway enzymes, both Ufsp1 mutants were born in normal ratios and did not exhibit gross phenotypic abnormalities. Despite the enrichment of Ufsp1 at neuromuscular junctions, only mild structural alterations of this synapse were detected, which did not impact overall muscle function. Our findings indicate that Ufsp1 is dispensable for normal development and homeostasis in mice, but further exploration of its function is needed in pathological conditions.